Profitability and Perception of Nepalese Farmers in Protected Vegetable Farming in Nepal - Sapkota, Dinesh; Subedi, Sandip; Subedi, Surendra (Agriculture Development Journal, 2022)
The study was conducted 7 districts of Nepal by selecting 90 respondents to understand profitability of vegetable farming under different type of protected structures namely temporary, semi-permanent and permanent. Descriptive statistics and scaling techniques were used to analyze data. The financial analysis showed significantly higher benefit cost ratio and payback period in temporary structures than that of semi-permanent and permanent structures. The net present value was found statistically similar in all types of protected structures. The age of household head and area under protected farming were found statistically higher among the adopters of temporary structure while the years of farm registration and experience in protected vegetable farming were found statistically higher among the adopters of semi-permanent structures. This shows graduation process of growers from temporary to semi-permanent structure. The productivity of vegetables under protected structure in the study area was found 191.55 mt./ha/year. The yield was found most satisfying factor, whereas the availability of technician was found to be the factor with highest index of difficulty. The findings of the study will have implication for the policy makers, suppliers and farmers regarding the promotion and adoption of different types of protected structures.